Status of basal stem rot disease on areca nut palm plantations in Kubu Raya District, West Kalimantan, Indonesia (Asian Journal of Agriculture, 2024)
Abstract. Supriyanto, Sulistyowati H, Arifin N. 2024. Status of basal stem rot disease on areca nut palm plantations in Kubu Raya District, West Kalimantan, Indonesia. Asian J Agric 8: 41-49. Areca nut (Areca catechu L.) is one of the leading plantation commodities with high economic value in West Kalimantan Province, Indonesia. One of the problems that affects the productivity of areca nut plantations is the presence of pathogen attacks, especially attacks by the fungus Ganoderma sp. which is the main pathogen in Arecaceae (palmae) plants. Ganoderma cause basal stem rot disease which is still difficult to control. The objective of this research was to determine the incidence level of basal stem rot disease and the diversity of fungi which cause disease in areca nut plantations in Kubu Raya District. The experiments were conducted using plant census methods and the collection of fruiting bodies of pathogenic fungi. The collected fungi were isolated, morphologically identified, and then confirmed it pathogenicity by Koch's postulates. The results showed that the incidence of areca nut basal stem rot disease in Kubu Raya District was relatively low (1.99%). The incidence of disease was found to be higher (4%) in poorly maintained plantations. A total of 5 types of fungi were found associated with areca nut basal stem rot disease, namely 3 types of Ganoderma sp., and 2 types of Trametes sp. However, only the type of Ganoderma has proven capable of causing disease in areca nut palm plants.
Keywords: Areca nut, basal stem rot, Ganoderma, Kubu Raya, Trametes